Saving CeeCee Honeycutt [compact disc, unabridged] : a novel - Hoffman, Beth (Penguin Audio, 2010)
Relegated to the care of an eccentric great-aunt after her mentally unbalanced mother's accidental death, twelve-year-old CeeCee is quickly surrounded by the strong women and cultural elements of her new Savannah community.